Tinjauan Fiqih Klasik atas Akad Qardh dan Transformasinya dalam Produk Digital Lending Syariah - Fitrah Amaliah Hasibuan; Muhamad Zen (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study discusses the qardh contract from a classical perspective and discusses the transformation of the practice of Sharia digital lending that is developing in the fintech era. Qardh is one type of approach to pious to Allah and is a type of mu'amalah that is characterized by assistance (ta'awun) to another party to meet their needs. In classical fiqh, Qardh is a loan contract with the condition that the borrowed and repaid are exactly the same and are returned at a time mutually agreed upon at the time of the contract without any excess when returning it. However, the development of financial technology has presented a capital for digital lending services in accordance with the concept of Sharia. This study aims to analyze the differences between the qardh contract in classical and contemporary fiqh, including its implementation in a contract in accordance with Sharia principles. The results of the study indicate that Sharia digital lending can use the qardh contract as a legal basis, but must still implement it with the principle of qardh hasan, namely avoiding elements of usury and gharar, and adapting to modern regulations. The form of the qardh contract in digital sharia lending products illustrates contemporary fiqh efforts in responding to the lives of modern society.